2022
DOI: 10.1002/gps.5719
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long‐term care service use by persons with dementia: A national dementia registry study conducted in Taiwan

Abstract: Background: This study investigated the determinants and use of Taiwan's longterm care (LTC) Plan Version 2.0 (LTC 2.0) services by persons with dementia (PWDs) and their caregivers. Methods: In total, 1268 PWD-caregiver dyads were enrolled for analysis from a national dementia registry. Andersen's Behavioral Model of Health Services Use was used to investigate the association of LTC service use with several factors, namely the demographic data of PWDs and their caregivers, migrant caregiver employment, monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The social resources include resources or services that PwD and their family caregivers can apply for, such as day care, home help services, responsive care and home care. Social resources provide additional support for families of PwD and ease the burden on caregivers (Tsai et al 2022;Wakefield 2020). Understanding family caregivers' utilisation of social resources may ease psychological distress.…”
Section: Social Resource Utilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The social resources include resources or services that PwD and their family caregivers can apply for, such as day care, home help services, responsive care and home care. Social resources provide additional support for families of PwD and ease the burden on caregivers (Tsai et al 2022;Wakefield 2020). Understanding family caregivers' utilisation of social resources may ease psychological distress.…”
Section: Social Resource Utilisationmentioning
confidence: 99%
“…Social resources provide additional support for families of PwD and ease the burden on caregivers (Tsai et al. 2022; Wakefield 2020). Understanding family caregivers' utilisation of social resources may ease psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…This study is a subproject of the National Dementia Registry Study (T-NDRS), which was conducted by the National Health Research Institutes of Taiwan and involved data collection from 2017 to 2019. 16 The T-NDRS was conducted at nine hospitals distributed across Taiwan: three in northern Taiwan, two in central Taiwan, and four in southern Taiwan. The inclusion criterion for individuals with dementia was individuals aged 50 to 90 years with a Clinical Dementia Rating (CDR) score of 0.5 or higher, denoting very mild dementia to severe dementia.…”
Section: Data Sources and Study Participantsmentioning
confidence: 99%
“…Factors such as dementia stage, capability of activity daily living (ADL), resource of informal and paid care, relationship between the care provider and the recipient, sociocultural context, and the LTC system design all needed to be considered (Morrisby et al, 2018 ; Shepherd-Banigan et al, 2021 ). A national dementia registry enrolled 1,268 Taiwanese and revealed that aberrant motor behaviors, dysfunction in ADLs, higher caregiver burden, not residing with family members, and not employing a migrant caregiver were the factors associated with LTC service usage (Tsai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%